TRANSFORMING LANGUAGE ASSESSMENT: A CASE STUDY ON ENHANCING LISTENING SKILLS EVALUATION FOR LANGUAGE LEARNERS - Dilrabo Babakulova (Western European Studies, 2024)
This study examines the transformation of language assessment through a case study focused on enhancing listening skills evaluation for language learners. Critiquing the original assessment's effectiveness in terms of practicality, reliability, validity, authenticity, and washback, the article proposes modifications to improve its efficacy. The modified assessment includes lead-in questions, detailed instructions, and a reflective writing task, aligning with established testing principles. Findings indicate that these modifications enhance task authenticity, comprehension, and student engagement, ultimately leading to a more effective assessment process
Keywords: Language assessment; test modification; test analysis